Responses of Root Endophytes to Phosphorus Availability in Peach Rootstocks With Contrasting Phosphorus-Use Efficiencies - Zhang, Yu; Liu, Xin; Guo, Jiying; Zhao, Jianbo; Wang, Shangde; Zheng, Zhiqin; Jiang, Quan; Ren, Fei (Frontiers in Plant Science, 2021)
Phosphorus (P) is an important macronutrient for all lives, but it is also a finite resource. Therefore, it is important to understand how to increase the P availability and plant uptake. The endophytes can help host plants to improve P uptake and will be apparently affected by plant genotypes. To investigate the mechanism of root endophytes in promoting P uptake of peach rootstocks, we analyzed the variations of the root endophytic fungal and bacterial communities of peach rootstocks with different P efficiencies under high or low level of P addition. Results showed that Proteobacteria were the dominant bacterial phylum in the roots of all rootstocks under the two levels of P addition. At low P level, the abundance of Actinoplanes in phosphorus-inefficiency root system was apparently higher than that at high P level. Actinoplanes produced important secondary metabolites, improving the stress resistance of plants. Under high P condition, the abundance of Ferrovibrio was higher in Qing Zhou Mi Tao than in Du Shi. Fe oxides considerably reduced the availabilityof applied P, which partially explained why the P utilization in Qing Zhou Mi Tao is inefficient. Further, Ascomycota was the dominant fungal phylum in the roots of all rootstocks under different levels of P addition. The fungi community of roots varied in different rootstocks at each P level, but was similar for the same rootstock at different P levels, which indicated that genotype had a greater effect than P addition on the fungal community of peach rootstocks.